Espaços e tempos de grupos escolares capixabas na cena republicana do início do século XX : arquitetura, memórias e história - Locatelli, Andrea Brandão (2012)
This paper investigates the historical construction of architectural projects for school groups in the process of creation and estabilishment in the state of Espirito Santo, 1908, seeking to understand them in their links with republican ideas and theories that circulated in the teaching Brazilian scenario in the early twentieth century. The study takes as its main analysis the Capixabas' architecture school groups from 1908 to 1930, to historically understand the configuration of spaces and times intended for the State Primary Schools, in the period previously mentioned. The power relations that constituted the political actions of those involved in the process of reform in the State's Public Education collaborated to understand how Capixabas produced a Republican spatial distribution of exemplary schools, which occurred between the voltages for the development of social organization and the possibilities of the place to advance in the economic modernity desired by the new regime, especially in the renewal of primary education in its specific areas. The study is based on a historiographical perspective that shifts the focus from analysis to systems of ideas that engendered the Republic in Brazil and Espirito Santo State and its conception of Public Education. Moreover, it connects these points to the political practices and social changes in the constitution of educational institutions of that period, especially in Espírito Santo. Thus, we use objects that bring brands of cultural practices of social actors involved in our procedures and the relationship between the production of documents and our problematizations selected for the survey are highlighted here. To this end, we seek the reflections of Michel de Certeau, Carlo Ginzburg and Marc Bloch to an understanding of a historiographical act that combines the historian's practice to his produced narrative. The sources were organized aiming to know the space and time allocated to educational institutions of the Republic, whose aesthetic and symbolism are expressed in a proposal of spreading Republican precepts. Although the spatial distribution of the first school groups in Espitiro Santo Sate have found economic difficulties mentioned in the documents of the government- political practices associated with the elitist and exclusionary character occurring in the locality- the State of Espirito Santo confirmed , on its way, the presence of those schools in the local scene using Republican symbolism , whose marks still remain in the State's buildings, not to mention the practical training of teachers and students